2022
DOI: 10.3390/children9111762
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Robot-Led Distraction during Needle Procedures on Pain-Related Memory Bias in Children with Chronic Diseases: A Pilot and Feasibility Study

Abstract: The current study evaluated the feasibility and preliminary clinical impact of robot-led distraction during needle procedures in children with chronic diseases on pain-related memories. Participants were 22 children (8–12 years old) diagnosed with a chronic disease (e.g., chronic immune deficiency) and undergoing a needle procedure as part of their routine treatment. Children were randomized to the experimental group (i.e., robot-led distraction) or control group (i.e., usual care). For feasibility, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In addition, although we did not find a significant difference in reducing experienced fear intensity compared to that associated with typical pain management, recent studies have supported the claim that socially assistive robots may have a long-lasting impact on affective outcomes caused by invasive procedural pain. Rheel et al [29] observed a medium effect size for pain intensity memory bias (Hedges' g = 0.70) and a very small effect size for pain-related fear memory bias (Hedges' g = 0.09) in favor of the robot-led distraction group. Robot-led distraction interventions could be promising methods for improving pain-related memory bias development but need to be investigated further.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, although we did not find a significant difference in reducing experienced fear intensity compared to that associated with typical pain management, recent studies have supported the claim that socially assistive robots may have a long-lasting impact on affective outcomes caused by invasive procedural pain. Rheel et al [29] observed a medium effect size for pain intensity memory bias (Hedges' g = 0.70) and a very small effect size for pain-related fear memory bias (Hedges' g = 0.09) in favor of the robot-led distraction group. Robot-led distraction interventions could be promising methods for improving pain-related memory bias development but need to be investigated further.…”
Section: Discussionmentioning
confidence: 98%